Improving the One-Step Flyback Microinverter Efficiency for Grid-Connected Solar Panel Using the Soft-Switching Method - Omid Ali Shojaei (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the development of industry across the world, the use of energy resources has widely increased. Solar energy has received more attention than other types of energy. Solar energy converters, the most common of which are microinverters, have two functions. First, the converter must track the maximum power operating point of the solar cell and place the solar cell at a maximum operating point. Second, it converts low-voltage DC to AC of the same voltage as the grid and inject a sinusoidal current into the grid. Today, numerous researches has been performed on microinverters, both in terms of control methods and of topology. The most important microinverters include flyback microinverters. In this article, different types of flyback microinverters were examined. Then, to remove the current problems, a new flyback inverter converter was introduced. The proposed inverter had an auxiliary circuit. The auxiliary circuit was simple and had only one auxiliary switch. The auxiliary circuit provides smooth switching conditions for the converter. The flyback converter switch and the auxiliary switch both turn on and off at zero current. Therefore, the converter efficiency increases as the switch stress and switching losses decrease. In this article, this inverter was fully investigated. Also, it was discussed how auxiliary circuit elements were designed and their converter switches were explained, and then a theoretical analysis of converters was confirmed using simulation findings.